Avaliação de uma potencial indicação geográfica na região sudeste do Tocantins: Biscoito Amor Perfeito de Natividade - Oliveira, Djales dos Santos (UFT, 2021)
Law 9,279 / 96 granted protection to Geographical Indications (IG), regulating them and providing sanctions for their violation. Through this intellectual protection instrument, this study aims to understand the importance of GI as an element of innovation and to evaluate the GI potential of the Amor Perfeito biscuit, a traditional product of Natividade, a municipality located in the Southeast Region of Tocantins. Product made from sweet sprinkles, refined sugar, coconut milk, butter and salt: a recipe created more than 100 years ago, with the differentials of its handcrafted production process, its hand-shaped crown shape and baked in a clay oven, as well as cultural and historical values that enrich the local cuisine. The research was carried out using the case study method, as it is a determined and unique phenomenon with the possibility of extensive exploration of the product. To achieve the research objectives, the procedures adopted were bibliographic research and data collection based on a systemic analysis carried out with secondary data from different institutions and organizations. Tocantins already has a Geographical Indication certification in the eastern region of the state with a natural product of unparalleled beauty: Capim Dourado do Jalapão. The possibility of granting a second certification in the southeastern region, through the artisanal biscuit Amor Perfeito, elevates Tocantins in the national scenario with emphasis on the protection of its intellectual property assets, in addition to other benefits directly related to the producer and the consumer through the aggregation of product value and increased sales, boosting the region's economy through job and income generation. As a result, it is expected to prove the feasibility of registering the Geographical Indication of the Amor Perfeito de Natividade (TO) cookie.